Kazimierz Przerwa-Tetmajer o Stanisławie Wyspiańskim - Grzelak, Izabela (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
Kazimierz Przerwa-Tetmajer and Stanisław Wyspiański were not only familiar, but first of all, rivals. The article presents fates of acquaintance two great artists at the turn of the 19th and 20th century. The author of this article concentrates on Tetmajer’s opinion about Wyspiański mainly.